2015
DOI: 10.1111/neup.12230
|View full text |Cite
|
Sign up to set email alerts
|

Adult‐onset cerebello‐brainstem dominant form of X‐linked adrenoleukodystrophy presenting as multiple system atrophy: case report and literature review

Abstract: X-linked adrenoleukodystrophy (X-ALD) is the most common peroxisomal disorder and is caused by ABCD1 mutations. A cerebello-brainstem dominant form that mainly involves the cerebellum and brainstem is summarized in a review of the literature, with autopsy confirmed cases exceedingly rare. We report a 69-year-old white man who was diagnosed with this rare disorder and describe neuropathologic, ultrastructural and genetic analyses. He did not have adrenal insufficiency or a family history of X-ALD or Addison’s d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…The differences in frequency might be related to ethnic and genetic factors as is the case with cerebellar ataxia in MSA—MSA‐C is more common in Japan than European countries or the United States . Other disorders that have cerebellar variants, such as adrenoleukodystrophy, also appear to be more frequent in Japan . Indeed, ethnic differences in frequency of the MAPT haplotype are well known .…”
Section: Discussionmentioning
confidence: 99%
“…The differences in frequency might be related to ethnic and genetic factors as is the case with cerebellar ataxia in MSA—MSA‐C is more common in Japan than European countries or the United States . Other disorders that have cerebellar variants, such as adrenoleukodystrophy, also appear to be more frequent in Japan . Indeed, ethnic differences in frequency of the MAPT haplotype are well known .…”
Section: Discussionmentioning
confidence: 99%
“…Heritable leukodystrophies with adult onset may present with ataxia, and neuropathologic examination may disclose characteristic lesions of the cerebellar white matter in adrenoleukodystrophy (OMIM 300100) (Ogaki et al, 2016), Alexander disease (OMIM 203450) (Spalke and Mennel, 1982; Stumpf et al, 2003), metachromatic leukodystrophy (OMIM 250100) (Guseo et al, 1975), Krabbe globoid cell leukodystrophy (245200) (Shao et al, 2016), and adult-onset dominant leukodystrophy (OMIM 169500) (Coffeen et al, 2000; Alturkustani et al, 2013). …”
Section: The Cerebellum In Lipid Storage Diseases and Leukodystrophymentioning
confidence: 99%
“…Among several phenotypes, it is reported that the olivopontocerebellar (OPC) form comprised 8.4% of all patients with ALD in Japan . The characteristic finding of the OPC form might be classified into the following: (i) Olivopontocerebellar atrophy (OPCA) type atrophy; (ii) dentate–rubral pathway involvement; and (iii) pontocerebellar pathway involvement . Here, we report an adult‐onset ALD patient with the OPC form.…”
Section: Introductionmentioning
confidence: 90%